2004
DOI: 10.1021/jp031188m
|View full text |Cite
|
Sign up to set email alerts
|

Micelles of Lipid−Oligonucleotide Conjugates:  Implications for Membrane Anchoring and Base Pairing

Abstract: This report examines the organization properties of new fluorescent DNA-lipids, either alone in water or in interaction with 1-octyl-beta-d-glucopyranoside micelles or egg phosphatidylcholine vesicles. We first describe the design and the syntheses of the conjugates. Then, we use UV-Vis absorption, steady-state fluorescence emission, electron microscopy, and fluorescence correlation spectroscopy after two-photon excitation to show that these DNA-lipids form spherical micelles in aqueous solution and incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 65 publications
1
57
0
Order By: Relevance
“…Under the same experimental conditions, the temporal evolution of the intensity I F (l Two-photon excitation: Our home-built two-photon excitation FCS setup has been previously reported. [56,63] Illumination is provided by a modelocked titanium-sapphire laser (Mira pumped by Verdi, Coherent) through a 60 , 1.2 NA water immersion objective (Olympus). The sample at 1 mm concentration was contained in a cuvette described in reference [56].…”
Section: Methodsmentioning
confidence: 99%
“…Under the same experimental conditions, the temporal evolution of the intensity I F (l Two-photon excitation: Our home-built two-photon excitation FCS setup has been previously reported. [56,63] Illumination is provided by a modelocked titanium-sapphire laser (Mira pumped by Verdi, Coherent) through a 60 , 1.2 NA water immersion objective (Olympus). The sample at 1 mm concentration was contained in a cuvette described in reference [56].…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the presence of two ether bonds in the structure of this LOC could be related to its homogeneous distribution in lipid membrane model systems, since ether-linked glycerophospholipids appear to be more loosely packed in membranes, thereby increasing their fluidity [49,50]. In contrast, the fact that Alexa 488-labeled C 28 -5′-ODN (compound 11) compound, that possess two neighboring alkyl chains, could be associated with model membranes is opposite to what it was observed by other authors who reported that a lipid-anchored oligonucleotide with two neighboring alkyl chains may tend to form stable supramolecular structures in an aqueous environment, making it difficult to insert into preformed membranes [51]. In that case the oligonucleotide was conjugated to a chalcone moiety bearing longer alkyl chains (2 × C 16 ) than those of C 28 -5′-ODN (2 × C 14 ).…”
Section: Binding Of Locs To Lipid Bilayer Systemsmentioning
confidence: 98%
“…Because of their amphiphilic properties they can form interesting supramolecular structures, such as monolayer films, micelles and/or vesicles, [1][2][3][4][5][6][7][8] organogels [5] or multilamellar layers. [5,8] Normally their nucleobases are exposed to the aqueous phase, and they potentially can form complementary Watson-Crick base pairs. [8][9][10] The lipophilic substituent can also act as an anchor for fixing lipophilic nucleosides or oligonucleotides in biocompatible lipid membranes, again by exposing the nucleotides to the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…[5,8] Normally their nucleobases are exposed to the aqueous phase, and they potentially can form complementary Watson-Crick base pairs. [8][9][10] The lipophilic substituent can also act as an anchor for fixing lipophilic nucleosides or oligonucleotides in biocompatible lipid membranes, again by exposing the nucleotides to the aqueous phase. [11][12][13][14] Recently we could show that nucleosides with lipid moieties linked to the nucleobase anchor in giant unilamellar vesicles (GUVs) and large unilamellar vesicles (LUVs) composed of unilamellar phospholipid bilayers.…”
Section: Introductionmentioning
confidence: 99%